Human resource development – A key factor for the sustainable development of Albania - Perlat Lame (Management : Journal of Contemporary Management Issues, 2004)
This article deals with the current situation of labor resources in Albania and its trends from the viewpoint of their contributions to the overall country progress. A real partnership between business and public institutions, the efforts to formalize the economy, to promote discipline and better application of international standards are considered key issues for the future country developments. The effective management of human resources and coordination could not be reached without profound structural and economic reforms, without free entrepreneurship initiative encouragement, and without mutual confidence between the employers and the employees.